Epigenetic effects of inhibition of heat shock protein 90 (HSP90) in human pancreatic and colon cancer. (28th August 2017) - Nagaraju, Ganji Purnachandra; Wu, Christina; Merchant, Neha; Chen, Zhengjia; Lesinski, Gregory B.; El-Rayes, Bassel F.
Abstract: Silencing of tumor suppressor and DNA repair genes through methylation plays a role in cancer development, growth and response to therapy in colorectal and pancreatic cancers. Heat shock protein 90 (HSP90) regulates transcription of DNA methyltransferase enzymes (DNMT). In addition, DNMTs are client proteins of HSP90. The aim of this study is to evaluate the effects of HSP90 inhibition on DNA methylation in colorectal and pancreatic cancer cell lines. Our data shows that inhibition of HSP90 using ganetespib resulted in downregulation of mRNA and protein expression of DNMT1, DNMT3A, and DNMT3B in HT-29 and MIA PaCa-2 cell lines. This in turn was associated with a drop in the fraction of methylated cytosine residues and re-expression of silenced genes including MLH-1, P16 and SPARC . These effects were validated in HT-29 tumors implanted subcutaneously in mice following in vivo administration of ganetespib. This work demonstrates the effectiveness of ganetespib, an HSP90 inhibitor in modulating DNA methylation through downregulation of DNMT expression. Highlights: DNA methylation involved in progression of pancreatic and colon cancer through silencing of key genes. Inhibition of HSP90 inhibited the growth of pancreatic and colorectal cancer cell lines with high baseline DNMT1 expression. Inhibition of HSP90 leads to downregulation of DNMT1, DNMT3a, DNMT3b and decrease in the frequency of DNA methylation. HSP90 inhibition induced expression of silenced p16, SPARC, and MLH-1 genes.